REMOVING “BOTTLENECKS” IN TRANSPORT INFRASTRUCTURE PROMOTES CONNECTIVITY IN THE MEKONG DELTA - Ha, Mai Thi Hong (Social Sciences Journal, 2023)
Regional integration is an inevitable requirement of a market economy and is the basis for sustainable socio-economic development. In regional links, regional transport infrastructure plays an extremely important role, determining the formation, development and improvement of the effectiveness of these links. The Mekong Delta has many potentials and advantages for development if regional connectivity is well implemented, although huge “bottlenecks” in transport infrastructure have hindered this process. Therefore, to promote regional connectivity and realize the goals in Resolution No. 13-NQ/TW of the Politburo, many synchronous solutions are needed. This article aims to clarify the role of transport infrastructure in inter-regions and the current status of “bottlenecks” in transport infrastructure in the Mekong Delta today and propose some basic solutions to solve the problem. This will help the Mekong Delta “take off”.